Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/abbs/gmab030
|View full text |Cite
|
Sign up to set email alerts
|

Liver kinase B1 attenuates liver ischemia/reperfusion injury via inhibiting the NLRP3 inflammasome

Abstract: Liver ischemia/reperfusion injury (IRI), a serious inflammatory response driven by innate immunity, occurs in liver surgeries such as liver resection and liver transplantation, leading to liver dysfunction, liver failure, and even rejection after transplantation. Liver kinase B1 (LKB1) plays a pivotal anti-inflammatory role in IRI. One of the most important factors involved in liver IRI is the aberrant activation of the nucleotide binding oligomerization domain like receptor (NLR) family, pyrin domain-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[14] Previous findings also confirmed that the NLRP3 inflammasome is activated in H/R-stimulated RAW264.7 cells. [15,36] HDAC6 inhibition is therefore required to reduce excessive downstream inflammatory responses. The HDAC6-specific inhibitor, TubA, can be used to treat HS [20,37,38] and inhibit NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Previous findings also confirmed that the NLRP3 inflammasome is activated in H/R-stimulated RAW264.7 cells. [15,36] HDAC6 inhibition is therefore required to reduce excessive downstream inflammatory responses. The HDAC6-specific inhibitor, TubA, can be used to treat HS [20,37,38] and inhibit NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cytokines, including TNF-α, IL-1β, and IL-6, were measured using their corresponding enzyme-linked immunosorbent assay kits (Beyotime) as reported in our previous studies [ 27 , 28 ] . According to the instructions, the kits were prepared in advance and left at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were monitored using a commercial microplate kit (JianCheng Bioengineering Institute, Nanjing, China) as reported in our previous studies [ 27 , 28 ] . After the reaction, NaOH was added and incubated at room temperature for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the cooperation between non-TLR molecules and the inflammasome pathway could be an attractive target for clinical intervention. This was addressed when high expression of liver kinase B1 (LKB1) correlated with decreased expression of the NLRP3 inflammasome via upregulation of FoxO1 and deactivation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) nuclear translocation [20]. Another group investigated the relationship between non-TLRs and TLRs and showed that modulation of TLR2, NOD1, and NOD2 led to decreased neutrophil infiltration in ischemic kidneys [21].…”
Section: The Intrinsic Relationship Between Nucleotide-binding Domain...mentioning
confidence: 99%